Innovative exploration of Hep-2 cell culture in the isolation and culture of Mycoplasma pneumoniae - Weiwei Wu; Wenwen Zhu; Jing Tong; Qiang Zhou; Yanping Xu; Xiuxiu Zhou; Yu Du; Jun Bi; Liguo Zhu (Infectious Medicine)
Background: The isolation and culture of Mycoplasma pneumoniae (MP) is time-consuming and has a low success rate. On the basis of the fact that cell lines are susceptible to MP contamination, we explored the possibility of using Hep-2 cell culture for the isolation and culture of MP, to overcome this long-standing technical problem. Methods: Quantitative Real-time PCR (qPCR) was used to detect MP in the nucleic acid samples of clinically suspected mycoplasma-infected patients. Positive samples were cultured in Hep-2 cells, with the classical commercial MP liquid culture medium serving as a control. For successful isolation of MP, the broth culture medium was used for subculture, then transferred to solid agar medium for isolation. The isolated strains were identified by nucleic acid and whole-genome sequencing. Results: Among the 20 throat swab samples collected from individuals with influenza-like illness, 10 MP-positive samples were detected by qPCR. Five strains of Mycoplasma were successfully cultured in Hep-2 cells within 7–10 days, while one strain was cultured in commercial MP broth after 21 days, with isolation rates of 50% and 10%, respectively. After repeated subculturing in liquid medium and inoculation onto solid medium, “fried-egg”-like colonies emerged. The isolated strains were identified by nucleic acid and whole-genome sequencing. Conclusions: The use of cell culture enables the rapid and effective isolation and culture of MP, addressing the long-standing challenge of MP cultivation. This advancement may contribute to improved antibiotic development, vaccine research, and the maintenance of global public health security.